2011
DOI: 10.1590/s0103-64402011000300012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different LED light-curing devices for bonding metallic orthodontic brackets

Abstract: The aim of this study was to assess the influence of different light-emitting diodes (LED) light-curing devices for bonding orthodontic brackets, using the shear bond strength and analysis of adhesive remnant index (ARI). Crowns from 60 bovine incisors received brackets bonded with Transbond XT. Specimens were divided into 4 groups (n=15) according to the light-curing procedures: HL = control, halogen light; OR = Ortholux LED; UL = Ultraled XP, and RD = Radii LED. All light-curing procedures were performed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
3
13
0
1
Order By: Relevance
“…The results showed that significant differences were observed between LED and QTH regardless of the thermocycling and silane condition. These results are in line with those of previous studies, which also found significant differences between QTH and LED units (8)(9)(10). Other study showed that photo-activation is dependent on the radiant exposure (16).…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that significant differences were observed between LED and QTH regardless of the thermocycling and silane condition. These results are in line with those of previous studies, which also found significant differences between QTH and LED units (8)(9)(10). Other study showed that photo-activation is dependent on the radiant exposure (16).…”
Section: Discussionsupporting
confidence: 93%
“…Regarding all kinds of light-curing systems, QTH lamps have long been predominant in dental practice. 9,14 In 1995, Mills was the first to suggest the use of LED in orthodontics. 15 While LED curing is a crucial step forward, refinements are being developed with the goal of faster and more powerful curing.…”
Section: Structural and Mechanical Analysis Of Three Orthodontic Adhementioning
confidence: 99%
“…Adhesive remnant index (ARI) scores 31,32) ranging from 0 to 3 were given as follows -0: No adhesive remained on tooth; 1: Less than 50% of adhesive remained on tooth; 2: More than 50% of adhesive remained on tooth; 3: All the adhesive remained on tooth.…”
Section: Adhesive Remnant Index (Ari) Measurementmentioning
confidence: 99%